Information technology of determination the company's financial condition for the financial planning subsystem of the EPM system - Moskalenko, Valentyna; Fonta, Natalia; Nikulina, Olena; Grinchenko, Marina; Yershova, Svetlana (National Aerospace University "Kharkiv Aviation Institute", 2022)
The subject matter of this article is the process of forming a company's development finance program. The goal is to develop the information technology to determine the company's financial condition for the financial planning subsystem of an enterprise performance management (EPM) System. The tasks are to develop a method for forming a company's development finance program as the basis for the financial planning subsystem of the EPM system; develop a methodology of determining the financial condition of the company as a component of the method; develop an information technology (IT) for determining the company’s financial condition; develop a method for forecasting financial states on the strategic period using a neural network. The following results were obtained. The method for forming a company's development finance program is implemented as the financial planning subsystem for the EPM system. A methodology for determining the financial condition of a company as a component of this method is presented in this article. Information technology for the implementation of this methodology has been developed. The components of the IT are the calculation of financial indicators based on data from financial statements for a certain period; the analysis of return on equity; the determination of the company financial stability; the determination of the financial condition in dynamics; the forecasting of the company's financial condition for the strategic period; the formation of development strategies for forecasting financial condition. The method for forecasting financial states in the strategic period was implemented using a neural network with the Temporal Fusion Transformer architecture. Conclusions. The scientific novelty of the results obtained is as follows: 1) the stages of the process of forming a company's development finance program were improved by methodology for determining the financial condition of the company, by model for determining the rational ratio of own and borrowed funds, by technology for selecting possible sources of financing development projects, by method for determining investment project financing schemes;2) methodology for determining the financial condition of the company was further developed by including a component for predicting financial indicators using a neural network; 3) the company's financial condition module for EPM System was further developed by IT implementation, which implements the assessment and forecast of the company's financial condition is carried out and the financial strategy of the company's development is formed. Предметом вивчення у статті є процес формування програми фінансування розвитку підприємства. Метою є розробка інформаційної технології визначення фінансового стану компанії для підсистеми фінансового планування системи управління ефективністю підприємства (EPM). Завдання, що вирішуються: розробити метод формування програми фінансування розвитку компанії як основу підсистеми фінансового планування EPM системи; розробити методологію визначення фінансового становища підприємства як складову частину методу; розробити інформаційну технологію (ІТ) визначення фінансового стану компанії; розробити метод прогнозування фінансового стану на стратегічному періоді з використанням нейронної мережі. Були отримані такі результати. Метод формування програми фінансування розвитку компанії реалізовано у вигляді модуля підсистеми фінансового планування для системи EPM. Розроблено методику визначення фінансового стану компанії як складову частину методу. Розроблено інформаційну технологію для реалізації даної методики. Компоненти ІТ: розрахунок фінансових показників на основі даних фінансової звітності за певний період; аналіз рентабельності капіталу; визначення фінансової стійкості підприємства; визначення фінансового стану в динаміці; прогноз фінансового стану компанії на стратегічний період; формування стратегії розвитку для прогнозованих фінансових станів. Метод прогнозування фінансового стану на стратегічний період реалізовано з використанням нейронної мережі з архітектурою Temporal Fusion Transformer. Висновки. Наукова новизна одержаних результатів полягає у наступному: 1) удосконалені етапи процесу формування програми фінансування розвитку компанії на основі методики визначення фінансового стану компанії, моделі визначення раціонального співвідношення власних та позикових коштів, технології вибору можливих джерел фінансування проектів розвитку та методики визначення схем фінансування інвестиційних проектів; 2) набула подальшого розвитку методологія визначення фінансового стану компанії за рахунок включення компонента прогнозування фінансових показників на основі нейронної мережі; 3) удосконалено модуль визначення фінансового стану компанії для EPM системи за рахунок реалізації ІТ, в якій реалізовано оцінку, прогноз фінансового стану компанії та формування фінансових стратегій розвитку компанії.
Інформаційна технологія визначення фінансового стану підприємства для підсистеми фінансового планування EPM системи
Keywords: strategic management; enterprise performance management system; financial condition; information technology; strategy; forecasting; neural network; стратегічний менеджмент; система управління ефективністю підприємства; фінансовий стан; інформаційні технології; стратегія; прогнозування; нейронна мережа